Some Jewish Women in Antiquity - Bar-Ilan, Meir (Brown Judaic Studies, 2020)
This book sets out to characterize different types of Jewish women in Eretz-Israel over an extended period of more than a thousand years, from the biblical period to the time of the Mishnah and Talmud. This is a study in the comparative history of the status of women in Eretz-Israel in antiquity, and, like any comparative study, it addresses the same issues in different circumstances, contributing to the relatively new field of Jewish social history; it also furnishes additional proof, should any be necessary, of the scientific momentum to be gained by interdisciplinary study like the present combination of history and the social sciences.